2021
DOI: 10.1016/j.scr.2021.102436
|View full text |Cite
|
Sign up to set email alerts
|

Non-permissive SARS-CoV-2 infection in human neurospheres

Abstract: Graphical abstract

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 103 publications
0
14
0
Order By: Relevance
“…SARS-CoV-2 has been detected in brain tissue, [ 106 , 115 , 116 ] including SARS-CoV-2 viral RNA transcripts [ 105 , 117 , 118 ], and viral proteins in the epithelial cells within the olfactory bulb [ 119 ]. However, on the other hand, studies showed that SARS-CoV-2 does not replicate in the CNS, and its CNS effects may be attributable to the immune responses that are triggered by the infection [ 120 , 121 ].…”
Section: Sars-cov-2 and The Nervous Systemmentioning
confidence: 99%
“…SARS-CoV-2 has been detected in brain tissue, [ 106 , 115 , 116 ] including SARS-CoV-2 viral RNA transcripts [ 105 , 117 , 118 ], and viral proteins in the epithelial cells within the olfactory bulb [ 119 ]. However, on the other hand, studies showed that SARS-CoV-2 does not replicate in the CNS, and its CNS effects may be attributable to the immune responses that are triggered by the infection [ 120 , 121 ].…”
Section: Sars-cov-2 and The Nervous Systemmentioning
confidence: 99%
“…Tissue samples showed a high viral load at seven days post-inoculation despite the absence of productive infection, as determined by analyzing supernatant samples. Similarly, non-productive (abortive) SARS-CoV-2 infections have been described in neural tissue [24,27]. Here, the presented data only provide initial insights and require further dissection of viral attachment or entry mechanisms.…”
Section: Discussionmentioning
confidence: 84%
“…Despite the numerous reports on COVID-19, it is still debatable if SARS-CoV-2 invades the Central Nervous System (CNS) via olfactory neurons (27) and infects neurons and glia of the CNS (28)(29)(30)(31)(32)(33)(34)(35). Different groups have shown that human neural progenitor cells, grown either as brain organoids or as neurospheres, are permissive to SARS-CoV-2 infection (30,(35)(36)(37)(38).…”
Section: Discussionmentioning
confidence: 99%